(untitled) (Environment & Health, 2016)
Objective. We assessed a state of the information of the population in the NPP surveillance zone on the consequences of nuclear power plant activity for the environment and its compliance with the existing information needs of the population residing near the objects of critical infrastructure. Materials and methods. The study was performed in the surveillance zone of the Rivne NPP in several directions: performance of the content analysis in separate editions of the press that are distributing at this territory; sociological survey of the adults on the information needs in the Rivne AP. We used the content analysis for the identification of the features of the information flow in 9 editions and 2 internet sites. 978 articles were analyzed according to the developed classifier for the period from January 2013 to August 2015. We have performed the sociological survey on the public awareness of the consequences of the NPP activity, the credibility of information sources and information needs among 220 persons in the surveillance zone of the Rivne NPP where a sampling error is 6.7%. Results. Content analysis of the selected media showed that a theme, connected with the activity of the Rivne NPP, was not topical and interesting for the journalists of all editions except specialized "Energy". Short news reports on the activities of the Rivne NPP, often provided by the NPP Information Centre (IC), prevail among the information flow. Publications of image character with neutral or positive tone predominate. The authorities do not use their opportunities to disseminate the information useful for the population and do not initiate the discussions on the critical environmental issues and subventions. Information field on the consequences of the NPP activity is forming under the powerful influence of IC NPP, which is directed on the creation of a positive image, but does not reflect all existing information needs of the community. The survey of the population indicates that there is a need of the information on the status of the background radiation (77.6%), the impact of the NPP on the environment (77.2%), detailed information on the conditions of storage and export of radioactive waste (45.2%) and a new reactor design solution (33.3%). Information nuclear strategy in the NPP surveillance zone requires a revision, taking into account a literacy in the radiation-hygienic issues and a risk degree of the residence near the nuclear cycle facility, a state of social activity and a readiness to accept one or the other information, guidelines for the health preservation, developments of the journalists who cover the emergencies.